2014
DOI: 10.2527/af.2014-0033
|View full text |Cite
|
Sign up to set email alerts
|

Meat produced by Japanese Black cattle and Wagyu

Abstract: Japanese Black Cattle and Wagyu In Japan, Wagyu cattle include four types of Japanese cattle: the Black, Brown, Shorthorn, and Polled breeds. All have played important roles locally and in the history of mixed farming, as well as the synergies that exist between cattle and crops, especially rice. Farmers gradually began replacing the role of cattle as draft animals with farm machinery and industrial fertilizers approximately 50 years ago, and in recent years, Japanese Wagyu cattle have been farmed more specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 68 publications
4
54
0
1
Order By: Relevance
“…Gotoh et al (2011) have compared intramuscular fatty acid composition of longissimus muscle in 26-month-old Japanese Black steers and Holstein steers reared and fattened using a standard fattening system (Table 1). In the longissimus muscle of Japanese Black steers, a higher percentage of unsaturated fatty acid was found than that in Holstein steers (Gotoh et al , 2014). Moreover, Gotoh et al (2011) have also compared the IMF content and fatty acid compositions of 21 major skeletal muscles using the same animals.…”
Section: Fatty Acid Composition Of Wagyu and Hanwoo Beefmentioning
confidence: 81%
See 2 more Smart Citations
“…Gotoh et al (2011) have compared intramuscular fatty acid composition of longissimus muscle in 26-month-old Japanese Black steers and Holstein steers reared and fattened using a standard fattening system (Table 1). In the longissimus muscle of Japanese Black steers, a higher percentage of unsaturated fatty acid was found than that in Holstein steers (Gotoh et al , 2014). Moreover, Gotoh et al (2011) have also compared the IMF content and fatty acid compositions of 21 major skeletal muscles using the same animals.…”
Section: Fatty Acid Composition Of Wagyu and Hanwoo Beefmentioning
confidence: 81%
“…The mean body weight and carcass weight of beef at slaughter (26-30 mon of age) were 725 kg and 470 kg, respectively. High performance marbled beef production has caused Japanese Black cattle to comprise the greatest share of Japan’s Wagyu cattle population (Albrecht et al , 2011; Gotoh et al , 2009; Gotoh et al , 2014). Recently, the IMF percentage of beef from Japanese Black cattle has an average value of greater than 30% (Albrecht et al , 2011; Horii et al , 2009).…”
Section: Wagyu and Hanwoo Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, fine, frost-like marbling is preferred and priced higher than coarse marbled beef (Motoyama et al, 2016). This has resulted in researchers developing camera systems to objectively measure marbling texture in Wagyu cattle through the "New Fineness Index", which measures the perimeter of marbling flecks (Gotoh et al, 2014). However, similar to the United States, marbling texture is not mentioned in the Japanese beef grading standards (Polkinghorne and Thompson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Intramuscular fat (IMF) or also called as marbling has been studied contributed to the beef palatability or eating quality of beef through its attributes such as flavour, juiciness and tenderness (Okumura et al, 2007;Hudson et al, 2015), even though several studies showed that the association between marbling score and beef palatability attributes was a positively small (Wheeler et al, 1994;Platter et al, 2003). However, marbling score has been used as one of major determinants for beef palatability in international markets especially in Japan, Australia and USA (Watson et al, 2008;Gotoh et al, 2014).…”
Section: Introductionmentioning
confidence: 99%